2013
DOI: 10.1007/s10803-013-1968-7
|View full text |Cite
|
Sign up to set email alerts
|

The Costs and Benefits of Self-monitoring for Higher Functioning Children and Adolescents with Autism

Abstract: The ability to regulate behaviors and emotions depends in part on the ability to flexibly monitor one’s own progress toward a goal. Atypical patterns of response monitoring have been reported in individuals with autism spectrum disorders (ASD). In the current study we examined the error related negativity (ERN), an electrophysiological index of response monitoring, in relation to behavioral, social cognitive, and emotional presentation in higher functioning children (8–16 years) diagnosed with autism (HFA: N =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 59 publications
2
23
0
Order By: Relevance
“…The average accuracy rate for the group was 75.15% ( SD = 17.37), which is comparable to that seen in ASD samples [Henderson et al, ; South et al, ]. Consistent with previous research in non‐ASD [Meyer, Hajcak, Torpey‐Newman, Kujawa, & Klein, ; Meyer et al, ] and ASD samples [Henderson et al, ], response time (RT) was faster for error ( M = 391.82 ms, SD = 82.86) compared to correct trials ( M = 523.27 ms, SD = 158.59; t (50) = 6.37 , P < 0.001), while post‐error RT was slower ( M = 509.98 ms, SD = 152.68) compared to post‐correct RT ( M = 492.78 ms, SD = 135.45; t (50) = −2.54, P < 0.05).…”
Section: Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…The average accuracy rate for the group was 75.15% ( SD = 17.37), which is comparable to that seen in ASD samples [Henderson et al, ; South et al, ]. Consistent with previous research in non‐ASD [Meyer, Hajcak, Torpey‐Newman, Kujawa, & Klein, ; Meyer et al, ] and ASD samples [Henderson et al, ], response time (RT) was faster for error ( M = 391.82 ms, SD = 82.86) compared to correct trials ( M = 523.27 ms, SD = 158.59; t (50) = 6.37 , P < 0.001), while post‐error RT was slower ( M = 509.98 ms, SD = 152.68) compared to post‐correct RT ( M = 492.78 ms, SD = 135.45; t (50) = −2.54, P < 0.05).…”
Section: Methodssupporting
confidence: 83%
“…To date, ten studies have been conducted that examine the ERN in ASD, some which provide inconsistent information regarding the relationship between the ERN and ASD symptoms. For example, though Henderson et al [] and Santesso et al [] found a larger ERN to relate to fewer ASD symptoms, Henderson et al [] found a larger ERN to relate to more ASD symptoms. By comparison, South, Larson, Krauskopf, and Clawson, [] found no relationship between ERN magnitude and ASD symptoms, and a more recent study found that the ERN was not correlated with ASD symptoms in family members of youth with ASD, nor in a control group [Clawson, South, Baldwin, & Larson, ].…”
Section: Additional Correlates Of the Ernmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, total CES scores (i.e., level of combat exposure), total CAPS scores (i.e., level of PTSD severity), and psychotropic medication status (yes/no; dummy-coded) were included as covariates in both models. The CRN was also included as a covariate to test whether the groups differed in ERN when controlling for potential differences in neural response to correct trials, consistent with prior studies (e.g., Henderson et al, 2015). The multilevel models used restricted maximum likelihood (REML) estimation and an unstructured covariance matrix.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Baron-Cohen and Hammer (1997) found that parents of children with Asperger syndrome did worse than controls on a theory of mind-related test – while in a study of healthy university students, Kunihira et al (2006) did not find a relation between results on a theory of mind test and a test of autistic tendencies – and Henderson et al (2015) found no difference between high functioning autistic participants and typical controls on theory of mind tasks.…”
Section: Buy a Dogmentioning
confidence: 99%